Household Portfolio Diversification: A Case for Rank-Dependent Preferences - Polkovnichenko, Valery (Review of Financial Studies, 2005)
The proliferation of novel preference theories in financial economics is hampered by a lack of non-experimental evidence and by the theories' additional complexity which has not been shown to be critical in applications. In this article I present arguments in support of preferences with rank dependency. Using the Survey of Consumer Finances data, I document two widespread patterns inconsistent with expected utility: (i) many households simultaneously invest in well-deversified funds and in poorly-diversified portfolios of stocks; and (ii) some households with substantial savings do not invest anything in equities. I show that portfolio choice models with rank-dependent preferences, plausibly parameterized and under fully rational assumptions, are quantitatively consistent with the observed diversification. These results call for further efforts to integrate the models of rank-dependent preferences in portfolio theory and asset pricing.